A Head-to-Head Comparison of an Isometric and a Concentric Fatigability Protocol and the Association With Fatigue and Walking in Persons With Multiple Sclerosis. (June 2020) - Taul-Madsen, Laurits; Dalgas, Ulrik; Kjølhede, Tue; Hvid, Lars G.; Petersen, Thor; Riemenschneider, Morten
Background . Fatigue is one of the most frequent symptoms in persons with multiple sclerosis (MS). Distinction is made between subjective perceptions of fatigue and objective measures of fatigability. Fatigability can be measured by different protocols. Yet no studies have compared isometric and concentric contraction protocols of the lower extremities head-to-head. Therefore, the purpose of the present study was to (1) compare 2 such protocols head-to-head and (2) to investigate the association between fatigability evoked by the 2 protocols and measures of fatigue and walking. Methods. A total of 45 patients with MS had their walking capacity measured objectively by the 6-minute walk test (6MWT) and subjectively by the 12-item Multiple Sclerosis Walking Scale (MSWS-12). Fatigue was measured by the Modified Fatigue Impact Scale (MFIS) and fatigability by 2 knee extension protocols: sustained isometric and concentric. Results. The sustained isometric protocol induced a higher degree of fatigability than the concentric protocol ( P < .01). Regression analyses revealed that sustained isometric fatigability was not associated with either measures of fatigue or walking (all r 2 = 0.00; P = .85-.99), whereas the concentric protocol was significantly associated with fatigue ( r 2 = 0.20; P < .01), 6MWT ( r 2 = 0.09; P < .05), and MSWS-12 ( r 2 = 0.16; P < .01). Furthermore, after adjusting for maximal strength and sex, concentric fatigability remained a strong and significant predictor of fatigue (β = 0.49) and walking (6MWT: β = −0.26; MSWS: β = 0.37). Conclusion. This study provides the first evidence that a lower-extremity concentric fatigability protocol provides superior reflection of both fatigue and walking when compared with a sustained isometric protocol. We suggest that concentric protocols should be the focus of future studies investigating fatigability.